RECIPROCITY IN THE ECONOMY OF THE AGE OF SILICON ECONOMY SYSTEMS TO EARLY EXPERIENCES CURRENT SOLIDARITY ECONOMY - Horacio, Simes (Visión de Futuro, 2012)
Reciprocity is an integrating principle of supportive economy activities. In non-capitalist societies, it has been realized through the participation of certain institutional arrangements that favored the stability of exchange relations. Progress towards capitalist societies and deepening them, dissolved many of these institutional supports, while economy relations separated from other social relations in which it was first inserted. In addition, the selfish individual was become an active participant in the economy life of society. With the construction of market economies and state regulation, reciprocal relationships were being reduced to a lower field activities. Under these circumstances, they should investigate how reciprocity is manifested today, the institutional arrangements that are suitable to give stability and unity to cooperative behavior and the dynamics of their relationship to the context of the market and the state.